Food insecurity and cardiovascular disease: Current trends and future directions - Ryan Chang; Zulqarnain Javed; Mohamad Taha; Tamer Yahya; Javier Valero-Elizondo; Eric J. Brandt; Miguel Cainzos-Achirica; Shiwani Mahajan; Hyeon-Ju Ali; Khurram Nasir (Elsevier, 2022)
Food insecurity (FI) - a state of limited access to nutritionally adequate food - is notably more prominent among patients with cardiovascular disease (CVD) than the general population. Current research suggests that FI increases the risk of cardiovascular morbidity and mortality through various behavioral and biological pathways. Importantly, FI is more prevalent among low-income households and disproportionately affects households with children, particularly those led by single mothers. These disparities necessitate solutions specifically geared towards helping these high-risk subgroups, who also experience increased risk of CVD associated with FI. Further, individuals with CVD may experience increased risk of FI due to the financial burden imposed by CVD care. While participation in federal aid programs like the Supplemental Nutrition Assistance Program and the Special Supplemental Nutrition Program for Women, Infants, and Children has been associated with cardiovascular health benefits, residual FI and lower dietary quality among many families suggest a need for better outreach and expanded public assistance programs. Healthcare systems and community organizations can play a vital role in screening individuals for FI and connecting them with food and educational resources. While further research is needed to evaluate sociodemographic differences in the FI-CVD relationship, interventions at the policy, health system, and community levels can help address both the burden of FI and its impacts on cardiovascular health.